Seeds of urbanism : palaeoethnobotany and the Indus Civilization - Weber, Steven
Within the Harappan or Indus Valley Civilization located in northwest South Asia, a dramatic shift towards more localized cultural units and away from urban complexes is thought to have begun at the end of the 3rd millennium BC. The reasons for decentralization and localization are still debated, but explanations often assume that a changing agricultural system was a causal factor in these processes (Kenoyer 1991; Jarrige 1985; Possehl 1986). This paper will focus on recently collected palaeoethnobotanical data from two sites, Harappa and Rojdi, which allow us to examine changes in agriculture during this critical time, and to understand how these changes are related to shifts in the socio-economic structure. Analysis suggests that while the types of plants at the two sites differed, the agricultural strategies in both places were changing in similar ways, The argument to be proposed is that the same socio-political and environmental issues were affecting inhabitants